(untitled) (Jurnal Teknologi (Sciences & Engineering), 2021)
The maturation stage of Cucumis sativus is among the important factors affecting its composition and quality. Hence, this study monitored the differences in total phenolic content (TPC), antioxidant activity, pigment and colour of Keningau-grown cucumbers (Cucumis sativus L.) at two stages of maturities, namely the semi-ripe (SR) and ripe (R). The colourimetric and spectroscopic findings revealed significant differences in the assessed variables (P < 0.05) in the two growth stages except for the pigment. The colour of semi-ripe cucumbers was of lower L* (33.39 ± 4.26) and a* (−10.00 ± 1.74) mean values, while the ripe cucumbers registered the corresponding mean values of 36.71 ± 2.85 and −8.90 ± 1.85. R cucumbers gave a higher mean b* coordinate (16.38 ± 3.16) over the SR ones (14.52 ± 2.52). Compositions of pigments, namely, chlorophyll-a (SR: 4.86 ±0.01 μg/mL, R: 3.55 ± 0.00 μg/mL), chlorophyll-b (SR: 2.12 ± 0.02 μg/mL, R: 1.79, 0.02 μg/mL) and total chlorophyll were higher in SR (6.98 ± 0.02 μg/mL) than R ( 5.34 ± 0.02 μg/mL) cucumbers, except for the composition of carotenoids (SR: 0.82 ± 0.01 μg/mL, R: 1.78 ± 0.01 μg/mL). The TPC in SR was higher (424.21± 5.32 mg/g) than the R ones (185.51±4.62 mg/g), with the corresponding antioxidant activity (IC50) for SR and R at 157.98 ± 1.57 and 191.66 ± 2.58 μg/mL, respectively. TPC and antioxidant activity between the SR and R cucumbers were negatively correlated (−0.992), which meant that not all phenolic compounds were involved in free radical scavenging.